Kinerja Badan Kesatuan Bangsa Dan Politik Kota Surabaya Dalam Pengawasan Organisasi Kemasyarakatan - Marshalena, Julia Azizah; Wibawani, Sri (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to evaluate the performance of the Badan Kesatuan Bangsa dan Politik (Bakesbangpol) in overseeing community organizations (ormas) in Surabaya. This evaluation aims to ensure that ormas operate within the legal framework and contribute positively to social stability and community development. The study highlights the importance of Bakesbangpol's role in mediating between the government and community organizations, thereby enhancing public participation in development processes and addressing challenges related to compliance with regulations. To achieve the study's objectives, a qualitative research methodology was employed, which included data collection through interviews, surveys, and direct observations. The researcher gathered reports from various ormas, conducted interviews with their leaders, and distributed questionnaires to participants to assess their satisfaction and the impact of the programs. The triangulation of data sources, including direct field observations, allowed for a comprehensive understanding of the effectiveness of the programs and the challenges faced by the organizations. The results of the study indicate that while Bakesbangpol has made significant strides in overseeing ormas, challenges remain in ensuring compliance with regulations and enhancing the effectiveness of programs. The findings reveal that some ormas struggle with awareness of legal requirements, which can lead to conflicts with government authorities. Additionally, the study suggests that Bakesbangpol's efforts in facilitating dialogue and providing support to ormas are crucial for fostering a collaborative environment. Overall, the evaluation underscores the need for ongoing monitoring and capacity-building initiatives to strengthen the role of ormas in community development and social harmony.